Selective and Wash‐Resistant Fluorescent Dihydrocodeinone Derivatives Allow Single‐Molecule Imaging of μ‐Opioid Receptor Dimerization. Issue 15 (7th January 2020) - Gentzsch, Christian; Seier, Kerstin; Drakopoulos, Antonios; Jobin, Marie‐Lise; Lanoiselée, Yann; Koszegi, Zsombor; Maurel, Damien; Sounier, Rémy; Hübner, Harald; Gmeiner, Peter; Granier, Sébastien; Calebiro, Davide; et al.
Abstract: μ‐Opioid receptors (μ‐ORs) play a critical role in the modulation of pain and mediate the effects of the most powerful analgesic drugs. Despite extensive efforts, it remains insufficiently understood how μ‐ORs produce specific effects in living cells. We developed new fluorescent ligands based on the μ‐OR antagonist E‐p ‐nitrocinnamoylamino‐dihydrocodeinone (CACO), that display high affinity, long residence time and pronounced selectivity. Using these ligands, we achieved single‐molecule imaging of μ‐ORs on the surface of living cells at physiological expression levels. Our results reveal a high heterogeneity in the diffusion of μ‐ORs, with a relevant immobile fraction. Using a pair of fluorescent ligands of different color, we provide evidence that μ‐ORs interact with each other to form short‐lived homodimers on the plasma membrane. This approach provides a new strategy to investigate μ‐OR pharmacology at single‐molecule level. Abstract : A pair of fluorescent, selective μ‐opioid receptor‐ligands was synthesized and applied in single‐molecule microscopy experiments. After their pharmacological characterization, the ligands were used to investigate diffusion behavior and homodimerization of wild‐type μ‐opioid receptors on the surface of living cells.